Physical and sensory properties of lemon-flavored acidic beverages formulated with nonfat dry milk during storage - Nan Li; Inseob Choi; Jennifer Vuia-Riser; Brandon Carter; MaryAnne Drake; Qixin Zhong (Journal of Dairy Science, 2022)
ABSTRACT: Sensory and physical properties of 2 lemon-flavored beverages with 5% and 7.5% wt/wt nonfat dry milk (NFDM) at pH 2.5 were studied during storage. The 2 beverages had similar volatile compounds, but the 5% NFDM had higher aroma and lemon flavor, with a preferred appearance by consumers due to the lower turbidity and viscosity. After 28 d of storage at 4°C, lemon flavor decreased in the 5% NFDM beverage but was still more intense than the 7.5% one. During 70 d of storage, no microorganisms were detected, and the beverages were more stable when stored at 4°C than at room temperature according to changes of physical properties measured for appearance, turbidity, color, particle size, zeta potential, rheological properties, and transmission electron microscopy morphology. Findings of the present study suggest that NFDM may be used at 5% wt/wt to produce stable acidic dairy beverages with low turbidity when stored at 4°C.